The Role of Educational Investment and Economic Openness in the Economic Growth of Member Countries of the Organization of Islamic Cooperation (OIC): - - Kurniawati, Sri; Saputra, Iqbal Irwandi Eka; Kurniasih, Erni Panca; Lestari, Nindya; Taimoor, Muhammad (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
There is complexity in the impact of education sector investment and international trade aspects, on economic growth among the Organization of Islamic Cooperation (OIC) member countries. This research aims to examine and analyze the influence of education investment, food exports and imports, and exchange rates on economic growth in five member countries of the Organization of Islamic Cooperation (OIC). The OIC member countries were determined as research objects because they have similarities in determining halal food as a condition for permitted food imports. The novelty of this research offers a fresh approach by thoroughly investigating these complex relationships, aiming to unveil their combined effects on economic growth, thus providing novel insights for decision-makers. The data used is a combination of time series data and cross-site data so testing begins with a stationary test and a cointegration test. The data span used includes 12 years. The results show that all the data used is stationary at the first difference level, and together or in groups all variables are cointegrated in the long term. Testing the hypothesis using the multiple linear regression method, it was found that education investment and exports had a positive effect on economic growth while imports and the exchange rate had a negative effect. The ability of these four variables to explain variations in changes in economic growth in the five OIC member countries is 72 percent and 28 percent is explained by other variables outside the model. The results of this research prove that the higher our dependence on food imported from abroad will reduce economic growth and conversely, if food exports can be increased it will increase the country's economic growth. This research has implications for international trade policy in increasing the economic growth of the five OIC member countries.